THE ROLE OF SOCIAL STUDIES TEACHERS IN PROMOTING THE VALUES OF CITIZENSHIP ACCORDING TO THE MODEL OF THE EUROPEAN CENTER FOR INTERDEPENDENCE AND GLOBAL SOLIDARITY FOR MIDDLE SCHOOL STUDENTS - Dr. Ahmed Abdul-Jabbar Ghaidan (American Journals, 2023)
This study aimed to identify the role of social studies teachers in promoting the values of citizenship according to the model of the European Center for Interdependence and Global Solidarity among middle school students,the descriptive survey method was used,in order to achieve the objectives of the research on promoting the values of citizenship for (the model of the European Center for Global Interdependence and Solidarity) (Cabizudo and others, 2012), the researcher adopted the tool that was used by (Ibrahim and Al-Hakmaniyah, 2022) in an Arabized form, consisting of a group of paragraphs amounting to 41 paragraphs, and includes three fields (knowledge, values, skills) and are compatible with the current research after ensuring its validity and stability by presenting it to a group of experts and specialists in the field of educational and psychological sciences, measurement and evaluation,the role of social studies teachers in promoting citizenship values according to the model of the European Center for Interdependence and Global Solidarity among middle school students was identified, according to educational qualifications and years of experience. The researcher used the tool consisting of (41) items distributed on three axes (knowledge, skills, and values). The current research community is limited to middle school social studies teachers for the academic year (2022-2023),and the sample of the study consisted of (115) teachers who were randomly selected within the Maysan Education Directorate. The fields of the model obtained the arithmetic averages according to the sequence (knowledge 2.89), (values 3.81), (skills 3.40), and in light of the results, the researcher drew several conclusions, including:1- The degree of enhancing citizenship values for teachers of social studies in the light of the model of the European Center for Interdependence and Global Solidarity came to a medium degree.2- There are no statistically significant differences according to the variables of educational qualification and years of experience.In light of this, the researcher made a set of recommendations, including:
Keywords: Social teachers, Reinforcement, citizenship values, Middle school students.